(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Congenital heart defects are an important problem in pediatrics due to their high prevalence and the need for early surgical correction due to significant health problems and disability in children. According to WHO, congenital heart disease occurs in 0.7-1.7% of newborns. In recent decades, the structure of cardiovascular pathology in childhood has changed significantly. Against the background of an increase in the number of cases of CHD, cardiac arrhythmias and conduction disorders, cardiomyopathies, the proportion of rheumatic diseases and infectious lesions of the myocardium decreased. CHD remains one of the leading causes of infant mortality, ranking second. In the perinatal period, congenital heart diseases cause 2.5% of deaths (0.25 cases per 1000 births), in the first year of life - 6-11% of deaths and about 50% of deaths associated with congenital malformations. In this regard, the issue of studying the epidemiology and risk factors for the development of congenital heart defects at an early age remains relevant and requires scientific research in this direction.